Swedish party programs and election manifestos - Språkbanken Text (University of Gothenburg, 2024)
The data for this corpus was retrieved from Svensk nationell
datatjänst.
All documents are also open a vailable at page: https://snd.gu.se/vivill, where it
is possible to search in the documents.
Swedish party programs and election manifestos builds on the "Vi vill …!
Hundra år av partipolitiska viljeyttringar" ("We want…! A hundred years
of political party declarations") project, which the predecessor of
SND, SSD, conducted in 2000–2002. The purpose of this project was to
collect the programs and manifestos that the political parties had
produced during the 20th century. In these texts, you can trace the
development of the political parties in terms of their language,
politics, and ideology. The material also provides an overview of which
questions have been essential for the development of Sweden.
The selection of election manifestos builds on work done by Sven-Olov
Håkansson in "Svenska valprogram 1902–1952" (”Swedish election programs
1902–1952”), and materials collected and used in the research
project "Partiernas opinionspåverkan" (“Political party influence on
public opinions”), POP, by Peter Esaiasson and Nicklas Håkansson. At
first, only political parties in the Swedish Parliament
(Sveriges riksdag) were represented in the material. Later additions
have given a broader selection of parties as well as party documents
related to the European Parliament elections.
In the case of party programs, we have searched in research libraries
and people’s movement libraries, as well as in the archives of the
political parties. As there is varying degrees of knowledge about which
programs have been produced, we are aware that we have probably been
unable to find an unknown number of documents that could otherwise have
been included in the collection.
This project was made possible thanks to John-Erik Ågotnes at NSD
(Norsk Samfunnsvitenskapelig Datatjenste, now SIKT), the Norwegian
counterpart to SSD, which in 1997 published a CD with Norwegian party
programmes. Ågotnes allowed SSD free use of the software he had
developed for his project.
The "Vi vill …" project was awarded financial support from the
Riksbankens Jubileumsfond grant for support to research
infrastructures.

Datan till den här korpusen är hämtad från Svensk nationell
datatjänst.
Dokumenten finns öppet tillgängliga via denna länk: https://snd.gu.se/vivill. Här går
också att söka i dokumenten.
Svenska partiprogram och valmanifest bygger på projektet "Vi vill....!
Hundra år av partipolitiska viljeyttringar" som genomfördes vid Svensk
samhällsvetenskaplig datatjänst (SSD) 2000-2002. Projektet syftade till
att sammanställa de partiprogram och manifest som de politiska
partierna producerat under 1900-talet. I dessa texter kan man spåra
partiernas utveckling, både vad gäller språkbruk, politik och ideologi.
De ger även en god överblick över de frågor som varit väsentliga för
vårt lands utveckling.
Samtliga partiprogram och valmanifest i databasen finns i .pdf och .txt
format. De finns även tillgängliga hos Språkbanken som en korpus vilket
medför ytterligare möjligheter för forskning på materialet.
Urvalet av valmanifest omfattade till en början endast riksdagspartier,
då det baserades på Sven-Olov Håkansson studie "Svenska valprogram
1902-1952" samt forskningsprojektet "Partiernas opinionspåverkan", POP,
av Peter Esaiasson och Nicklas Håkansson. Materialet har sedan
kompletterats och urvalet har breddats till att exempelvis omfatta
dokument för Europaparlamentet samt för partier utanför riksdagen.
Fortfarande saknas ett okänt antal dokument som skulle kunna ingå i
samlingen.
Svenska partiprogram och valmanifest
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik